Annexin A6 is highly abundant in monocytes of obese and type 2 diabetic individuals and is downregulated by adiponectin in vitro - Stögbauer, Fabian (Korean Society of Medical Biochemistry and Molecular Biology, 2009)
Adiponectin stimulates cholesterol efflux in macrophages and low adiponectin may in part contribute to disturbed reverse cholesterol transport in type 2 diabetes. Monocytes express high levels of annexin A6 that could inhibit cholesterol efflux and it was investigated whether the atheroprotective effects of adiponectin are accompanied by changes in annexin A6 levels. Adiponectin reduces annexin A6 protein whereas mRNA levels are not affected. Adiponectin-mediated activation of peroxisome proliferator-activated receptor α (PPARα) and AMP-activated protein kinase (AMPK) does not account for reduced annexin A6 expression. Further, fatty acids and lipopolysaccharide that are elevated in obesity do not influence annexin A6 protein levels. Annexin A6 in monocytes from overweight probands or type 2 diabetic patients is significantly elevated compared to monocytes of normal-weight controls. Monocytic annexin A6 positively correlates with body mass index and negatively with systemic adiponectin of the blood donors. Therefore, the current study demonstrates that adiponectin reduces annexin A6 in monocytes and thereby may enhance cholesterol efflux. In agreement with these in vitro finding an increase of monocytic annexin A6 in type 2 diabetes monocytes was observed.